Survey of GIS Implementation and Use within Smaller Academic Libraries - JaNae Kinikin; Keith Hench (Issues in Science and Technology Librarianship, 2005)
This paper describes a survey of the implementation and use of Geographic Information Systems (GI) in smaller academic libraries (Carnegie Classification Master's Colleges and Universities I & II) (Carnegie Foundation 1997-2003). Two hundred, sixty-eight libraries were surveyed and 138 surveys were returned. We sought to determine to what degree smaller schools have adopted GI and how the implementation of GI was accomplished. The survey focused on hardware/software, staffing, levels of service, training, monetary support, and use. Twenty-two smaller academic libraries have adopted GI and 27 plan to incorporate this technology in the near future. This analysis will focus specifically on those libraries that already have adopted GI. [ABSTRACT FROM AUTHOR]